BASIS OF APPROACH FOR CREATING TECHNOLOGY FOR CYBER DEFENCE OF VIDEO INFORMATION RESOURCES IN THE INFOCOMMUNICATION SPACE - Бараннік, В. В.; Підлісний, С. А. (Science-based technologies, 2016)
Consider the placing technology of variable length codes in the slots of equal length with modern threats in information and telecommunication systems. Displaying effect distortion variable length codes adopted by the integrity of video information resource. The process of restoration of picture elements if errors in accepted slot. Substantiated conditions for efficient coding in using of slots technology of variable length codes.